2016
DOI: 10.1097/j.pain.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the prevalence of chronic widespread pain in the general population

Abstract: One in 10 adults report chronic widespread pain with potential sociocultural variation. Cultural differences in pain reporting should be considered in future research.Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
226
4
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(259 citation statements)
references
References 32 publications
(79 reference statements)
15
226
4
2
Order By: Relevance
“…10,16 The combined 5-year prevalence of recurrent regional pain consultation ("unrecognized" CWP) and nonspecific pain complaints ("recognized" CWP), after excluding specific generalized musculoskeletal diagnoses, was slightly higher, at 13%, than general population point prevalence estimates for CWP (10%). 26 Combined with our findings from Phase 2, this indicates that prevalence of widespread pain based on consultation data may give similar prevalence estimates to general population surveys based on strict CWP criteria, but will not represent an identical group of people.…”
Section: Nonmutually Exclusive Groupssupporting
confidence: 52%
See 2 more Smart Citations
“…10,16 The combined 5-year prevalence of recurrent regional pain consultation ("unrecognized" CWP) and nonspecific pain complaints ("recognized" CWP), after excluding specific generalized musculoskeletal diagnoses, was slightly higher, at 13%, than general population point prevalence estimates for CWP (10%). 26 Combined with our findings from Phase 2, this indicates that prevalence of widespread pain based on consultation data may give similar prevalence estimates to general population surveys based on strict CWP criteria, but will not represent an identical group of people.…”
Section: Nonmutually Exclusive Groupssupporting
confidence: 52%
“…26 Threequarters of recurrent regional pain consulters did not have a code recorded for generalized pain conditions related to CWP (eg, fibromyalgia). They therefore had widespread pain potentially unrecognized as such by their GP.…”
Section: Nonmutually Exclusive Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal pain affects about 12% of the general population, with the proportion of women being generally twice as high compared to men [2]. CWP is a diagnosis that challenges the social and cultural boundaries of current perception of illness and health in the Western world and the lack of a biomedical diagnosis denies the sufferer's legitimacy of the "sick role".…”
Section: Introductionmentioning
confidence: 99%
“…According to ACR 1990 criteria, the prevalence of CWP is approximately 10% in the general population [25,26], with a 1.2-5.4% prevalence for the FM subgroup per the ACR 1990, 2010, and the modified 2010 criteria [27]. In 2010, The Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU) revealed that the Swedish population's prevalence for persistent pain to be about 40% and that about 5% of these people sought health care and about 1% sought specialist care.…”
Section: Chronic Pain Is a Public Health Challengementioning
confidence: 99%